Prediction scenarios of past, present, and future environmental suitability for the Mediterranean species Arbutus unedo L. - Almeida, Alice Maria (2022)
Climate change is a challenge for forests in the coming decades, with a major impact on species adaptation and distribution. The Mediterranean Basin is one of the most vulnerable hotspots for biodiversity conservation under climate change in the world. This research aimed at studying a Mediterranean species well adapted to the region: the Arbutus unedo L. (strawberry tree). The MaxEnt, a presence-only species-distribution software, was used to model A. unedo’s environmental suitability. The current species potential distribution was accessed based on actual occurrences and selected environmental variables and subsequently projected for the Last Glacial Maximum (LGM), the Mid-Holocene (MH), and the years 2050 and 2070, considering the two Representative Concentration Pathways: RCP4.5 and RCP8.5. Results from the LGM projection suggest the presence of refugia in the core of the Mediterranean Basin, in particular the Iberian Peninsula (IP). The projections for the MH indicate increasing climatic suitability for the species and an eastward expansion, relatively to LGM. The predicted future environmental changes will most likely act as a catalyst for suitable habitat loss and a range shift towards the North is likely to occur